Dielectrophoresis-Based Positioning of Carbon Nanotubes for Wafer-Scale Fabrication of Carbon Nanotube Devices - Kimbrough, Joevonte (Micromachines (Basel), 2020)
In this paper, we report the wafer-scale fabrication of carbon nanotube field-effect transistors (CNTFETs) with the dielectrophoresis (DEP) method. Semiconducting carbon nanotubes (CNTs) were positioned as the active channel material in the fabrication of carbon nanotube field-effect transistors (CNTFETs) with dielectrophoresis (DEP). The drain-source current (I(DS)) was measured as a function of the drain-source voltage (V(DS)) and gate-source voltage (V(GS)) from each CNTFET on the fabricated wafer. The I(DS) on/off ratio was derived for each CNTFET. It was found that 87% of the fabricated CNTFETs was functional, and that among the functional CNTFETs, 30% of the CNTFETs had an I(DS) on/off ratio larger than 20 while 70% of the CNTFETs had an I(DS) on/off ratio lower than 20. The highest I(DS) on/off ratio was about 490. The DEP-based positioning of carbon nanotubes is simple and effective, and the DEP-based device fabrication steps are compatible with Si technology processes and could lead to the wafer-scale fabrication of CNT electronic devices.